Practitioner Profile: An Interview with Andrea Vining - Andrea Vining (Journal of Financial Therapy, 2015)
Andrea Vining is a Financial Advisor at Morgan Stanley in Pasadena, California who was named to the Firm’s Pacesetter’s Club in 2015, a global recognition program for Financial Advisors who, within their first five years, demonstrate the highest professional standards and first class client service. She holds a Bachelor of Arts degree in Literature from the University of California at Santa Cruz and her interest in the arts is personal and life-long. She studied Jewelry Design & Fabrication at the Gemological Institute of America in Carlsbad, CA and is also a certified bench jeweler. She and her colleagues are passionate about leveraging their network to help others achieve their financial, philanthropic, and life goals.
Keywords: financial therapy; financial advising